Bortezomib‐Based Antibody Reduction Therapy: The First Step to "True" Desensitization?. Issue 1 (22nd December 2014) - Budde, K.; Lehner, L. J.
<x xml:space="preserve">Abstract</x> This editorial discusses weaknesses and strengths of a novel bortezomib‐based desensitization strategy, including the inherent problems of Luminex single antigen bead technology in determining treatment effect, and the advantages and limitations of the adaptive multiphase treatment design used by Woodle et al (page 101).